2014
DOI: 10.1002/cbic.201402439
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA G‐Quadruplexes with Helical Small Molecules

Abstract: We previously identified quinoline-based oligoamide helical foldamers and a trimeric macrocycle as selective ligands of DNA quadruplexes. Their helical structure may permit the targeting of the backbone loops and grooves of G-quadruplexes instead of the G-tetrads. Given the vast array of morphologies G-quadruplex structures can adopt, this may be a way to elicit sequence selective binding. Herein, we describe the design and synthesis of molecules based on macrocyclic and helically folded oligoamides. We tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 68 publications
0
28
0
1
Order By: Relevance
“…DNA G-quadruplexes have been attacked with aromatic oligoamides [138]. Considerable interactions were observed between the foldamers and the DNA.…”
Section: Aromatic Oligoamidesmentioning
confidence: 99%
“…DNA G-quadruplexes have been attacked with aromatic oligoamides [138]. Considerable interactions were observed between the foldamers and the DNA.…”
Section: Aromatic Oligoamidesmentioning
confidence: 99%
“…However, they have a higher incidence in promoters of oncogenes and telomeres2122. Thus, many studies exploited these G-quadruplexes as rational targets for anticancer therapy23242526. Since complex 1 has been shown to bind selectively to the telomeric quadruplex, we decided to investigate its binding affinity to G-quadruplex forming sequences in selected well-established oncogene promoters and cancer-related genes using Fluorescence Intercalator Displacement (FID) titrations.…”
Section: Resultsmentioning
confidence: 99%
“…These techniques include single-molecule Förster resonance energy transfer (smFRET) (48, 5759, 64, 74, 77, 80, 81, 110, 124), optical tweezers (26, 27, 54, 98), magnetic tweezers (125, 126), combined smFRET–magnetic tweezers (63), atomic force microscopy (AFM) (66), tethered particle motion assays (18, 62), and protein nanopores (46, 102, 119). Each approach comes with its own advantages and drawbacks; however, the most widely employed experiments to date have used smFRET or optical/magnetic tweezers.…”
Section: Telomere Dna Structure and Dynamicsmentioning
confidence: 99%
“…As such, it has remained a major challenge to develop GQ-binding ligands with the high affinity and specificity required for therapeutic applications. Excitingly, a recent smFRET study reported the binding behavior of a novel class of small helical compounds that bind telomere GQ structure through a series of spatially specific backbone interactions, resulting in binding affinities on par with the best GQ-binding ligands to date (74). …”
Section: Telomere Dna Structure and Dynamicsmentioning
confidence: 99%